Estimasi Stok Karbon di Kawasan Penambangan Akibat Perubahan Luas Penutupan Lahan Terkait dengan REDD - M. Lutfi; Harry Tetra Antono (Program Studi Statistika Unisba, 2014)
Deforestation and forest degradation caused by mining has had very great impact to global climatechange, because one of the functions of forest vegetation is very important is capture and storageCO2 emissions. Revegetation activities in the area of mining is done in order to restore the forestvegetation. Research to estimate absorbtion CO2 as a result of carbon stock by forest vegetationneeds to be done . Remote sensing technology through radar imagery can be applied to estimateforest vegetation carbon stock more quickly and efficient. The research was conducted in the goldmining area of PT . JResources Bolaang Mongondow. Main objective of this research is to estimatechanges in forest covered land due to mining activities, estimation amount of carbon stored in 2008 ,2009, and 2010 and the economic value that can be obtained from stored carbon, using theestimated price based REDD schemes. The methodologies for measurements of the variables used inthe calculation variable of above ground biomass using allometric and ALOS PALSAR image analysisof 2008, 2009, and 2010 to estimate the carbon stock in forests. The results showed there werewidespread changes in forest land cover due to mining activities, and based on image analysis of2008 , 2009, and 2010 , the amount of carbon stock in the research area respectively are32,695,253.57 ton C, ton C 50,146,772.71 and 79,420,248.55 ton C. The economic value of carbonstock in 2010 are Rp.7,538,299,190,029.09 with price estimates and assumptions based on REDDscheme BAU Carbon savings in 2008.